El desarrollo del pensamiento lógico – matemático en niños del subnivel 2 de educación inicial unidad educativa Gabriela Mistral - Iza Pila, Elizabeth Alexandra (2023)
The research project analyzes the logical-mathematical thinking development in Initial Sublevel 2 children at Gabriela Mistral Educational Unit. The goal research is to diagnosis to determine the logical-mathematical thinking development’s level. The methodology is qualitative, descriptive exploratory type in such a way that the project straight out to be viable and applicable. The techniques applied were the interview to the teacher and pedagogical assistant and the observation with the observation sheet instrument to the Initial 2 children in their classroom. According to the global results obtained, 44% of children have acquired mathematical relationships according to the Initial Level 2. In the same way, 53% of the group that is in the process of reaching the level will continue; and 3% who have not reached the required level. This is in agreement with the skills planned in the learning results dictated by the Curriculum established with the Education Ministry which suggests the application of new strategies in the classroom in order to promote the mathematical logical thinking development. The results found is the support to improve the teaching-learning process in which ICTs can occupy a significant place for all children’ care according to their needs and particularities.